Development of BioPhy Magazine Containing Local Wisdom to Improve Problem Solving Ability and Promote Environmental Awareness Campaign - Lutfiyanti Fitriah; Ita Ita (Jurnal Penelitian Pendidikan IPA, 2022)
The purpose of this study was to describe the validity and effectiveness of BioPhy Magazine based on local wisdom, which was developed to improve problem-solving skills and encourage students to conduct environmental awareness campaigns. This type of research was development research with the Tessmer formative evaluation model. The small group trial subjects are Chemistry Tadris students who are taking Basic Physics courses in the 2021/2022 academic year. Data were obtained through validation sheets, problem-solving tests, and poster assessment sheets. The data were then analyzed using the Aiken formula, N-gain, effect size, and Wilcoxon test. The results of the analysis showed that the developed magazine was valid from the aspect of content, presentation, and language. Magazines were also effective in improving problem-solving skills, with an N-gain score on the small group test of 0.90 with a high category and an effect size of 3.34 with a strong influence category. In addition, based on the Wilcoxon test, it was known that Asymp. Sig. (2-tailed) of 0.005, which meant that there was a significant difference in problem-solving ability between before and after learning. In addition, magazines could encourage students to carry out environmental awareness campaigns as indicated by the average student environmental poster score of 95.38. So, BioPhy Magazine was valid, effective, and successful in encouraging students to carry out environmental awareness campaigns